Numerical analysis of thermo-sensitive cavitating flows with special emphasises on flow separation and enstrophy conversion. (June 2021) - Liu, Yaoyao; Li, Xiaojun; Lin, Zhe; Li, Linmin; Zhu, Zuchao
Abstract: The objectives of this paper are to investigate the flow separation and its effects on the characteristics of enstrophy conversion in a thermo-sensitive cavitating flow. Simulated results indicate the correlation exists in the flow separation and re-entrant-jets can be well depicted by the application of boundary vorticity dynamics theory (BVDT ). The distributions and first-order moment of the wall vorticity demonstrate that the shedding, collapse and reattachment of cavity enhance the effect of vorticity. To reveal the evolution mechanism and distribution characteristics of enstrophy, various terms of enstrophy are established. As demonstrated by the results, the enstrophy production term (EPT ) dominates the entire energy evolution process, and it is distributed in the interface of the cavity where intensive mass transfer exists. The enstrophy viscosity dissipation term (EVDT ) always reduces enstrophy and inhibits energy loss. The impacts of the other two terms on absolute enstrophy are limited due to the smaller numerical integration. Furthermore, the attachment sheet cavity suppresses the development of various terms because of the stationary flow field. Whereas the multiscale detachment or collapse of cavity lead to a rapid increase in enstrophy, which manifests as the energy loss becomes evident.